2020
DOI: 10.1108/bfj-06-2020-0522
|View full text |Cite
|
Sign up to set email alerts
|

Food allergy knowledge, attitudes and practices (KAP) among restaurant's staff in Jordan: a cross-sectional study

Abstract: PurposePeople with food allergies rely to a great extent on restaurant staff to have a safe meal. The purpose of this paper is to acquire novel data to evaluate knowledge, attitudes and practices of food allergy among the restaurant's staff and factors that could be associated with these domains.Design/methodology/approachA cross-sectional study involving 306 restaurant staff in Amman City, Jordan was conducted using a validated self-reported questionnaire. Logistic regression analysis was performed to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…This is in agreement with results of other studies, which stated that having a higher level of education was associated with a greater knowledge of food allergies and food labelling. 11 , 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with results of other studies, which stated that having a higher level of education was associated with a greater knowledge of food allergies and food labelling. 11 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with a Jordanian study where females had better attitudes towards food allergies than males. 11 This is due to females having higher levels of empathy and being more invested in nutritional issues than males. 25 Those aged 18 to 34 were found to check nutritional claims related to food allergies more frequently than other age groups (p-value = 0.021) as seen in Table 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The significant associations between attitude and age in the present study are consistent with a study conducted in Jordan, which indicated that school personnel who were older or potentially who had more years of experience, were associated with more positive attitudes. 44 Attitude represents beliefs that can act as an agent between knowledge and practice, 45 and selfefficacy can be improved through food allergy training and education workshops. 40 This may be one of the reasons for the negative level of attitude shown in the present study because only 26.4% of the participants had attended food allergy training.…”
Section: Attitude Itemmentioning
confidence: 99%
“…In Alexandria, Egypt, a developed self-administered questionnaire derived from previous related studies to assess food allergy KAP among restaurant employees (e.g. Ajala et al, 2010;Loerbroks et al, 2019;Elsahoryi et al, 2021). An independent translator with substantial experience in tourism and hospitality education developed the questionnaire in English and then translated it into Arabic.…”
Section: The Questionnaire Designmentioning
confidence: 99%
“…The study revealed that 58% of respondents had not received any training on food allergies, while 35% believed that high heat could destroy allergens, and 25% believed that allergens could be safely removed from finished meals. This lack of knowledge could prevent food service employees from accommodating customers or responding to their questions and special requests appropriately (Shafie & Azman, 2015;Dupuis et al, 2016;Radke et al, 2016;Elsahoryi et al, 2021;Nasseredine et al, 2021). Also, non-coordinated employees may not follow safe food handling procedures in the kitchen if they are unaware of the severity of allergies.…”
Section: Introductionmentioning
confidence: 99%